2010
DOI: 10.1021/am1008826
|View full text |Cite
|
Sign up to set email alerts
|

Photopatternable Poly(4-styrene sulfonic acid)-Wrapped MWNT Thin-Film Source/Drain Electrodes for Use in Organic Field-Effect Transistors

Abstract: We describe the cross-linking of poly(4-styrene-sulfonic acid) (PSS) by exposure to ultraviolet (UV) light (λ = 255 nm) under a vacuum. Fourier transform infrared (FT-IR) spectroscopy and X-ray photoelectron spectroscopy (XPS) showed that the photo-crosslinking of PSS resulted from coupling between radicals that were generated in the polymer chains by UV excitation. The photo-cross-linkable characteristics of PSS were employed to fabricate solution-processable, photopatternable, and conductive PSS-wrapped mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…This phenomenon is similar to the effect of increasing the degree of crosslinking in the previous session. The results indicate that a higher degree of PSS crosslinking is achieved with a longer UV irradiating time which is in good agreement with the literature [37]. An increase in UV irradiating time from 2 to 4 h results in a substantial decrease in reverse salt flux while only a slightly decrease is observed in water flux when using 0.5 M NaCl as a draw solution.…”
Section: Effect Of Crosslinking To the Lbl Membrane's Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…This phenomenon is similar to the effect of increasing the degree of crosslinking in the previous session. The results indicate that a higher degree of PSS crosslinking is achieved with a longer UV irradiating time which is in good agreement with the literature [37]. An increase in UV irradiating time from 2 to 4 h results in a substantial decrease in reverse salt flux while only a slightly decrease is observed in water flux when using 0.5 M NaCl as a draw solution.…”
Section: Effect Of Crosslinking To the Lbl Membrane's Performancesupporting
confidence: 91%
“…Moreover, the crosslinking of PSS is also proven by the decrease in the intensity of the stretching vibration peaks of the -SO 3 group as shown in Fig. 14; [37].…”
Section: Ftir Characterizationmentioning
confidence: 91%
See 1 more Smart Citation
“…In order to circumvent the solubility problems, PSS and other electrolytes have been adopted to make soluble formulations of MWCNT. Electrodes were fabricated based on PSS‐wrapped MWCNST, showing the interesting feature of being photopatternable 148. Their compatibility with solution processed TIPS‐pentacene (TIPS‐p) was demonstrated yielding high‐mobility OFETs.…”
Section: Charge Injection In Ofetsmentioning
confidence: 99%
“…Nagata et al 48 have clarified the respective effects of UV light irradiation and exposure to ozone gas on the properties of PEDOT:PSS. 48 Hong et al 50 have reported that there are two kinds of bonds in PSS that can be broken under UV exposure: the cleavage of a a-hydrogen bond generates polystyrene radicals, and the second cleavage happens between the sulfonic acid group and the phenyl group. Xing et al 49 describe a simple method to increase the conductivity of the PEDOT:PSS film by exposure to UV light in a vacuum.…”
Section: View Article Onlinementioning
confidence: 99%